Can Policy Packaging Help Overcome Pigouvian Tax Aversion? A Lab Experiment on Combining Taxes and Subsidies - Gøril L. Andreassen; Steffen Kallbekken; Knut Einar Rosendahl (Center for Economic Studies and ifo Institute (CESifo), 2023)
Tax aversion makes it politically challenging to introduce Pigouvian taxes. One proposed solution to overcome this resistance is to package policies. Using an online lab experiment, we investigate whether combining a tax and a subsidy is perceived as more acceptable than the tax or the subsidy alone. The purpose of the policies is to reduce demand for a good with a negative externality to the socially optimal level. We find that support for a combination of a tax and a subsidy equals the simple average of support for the two instruments alone. Combining a tax and a subsidy therefore does not reduce tax aversion, other than through lower tax rates in the combinations. We also examine potential mechanisms behind the tax aversion. Participants hold more pessimistic beliefs about what share of the tax revenue they will receive when the tax is implemented alone than when it is combined with a subsidy. Furthermore, we find that the participants expect the tax to be more effective in reducing demand for the good with a negative externality than both the subsidy alone and the combinations of tax and subsidy. This belief does not, however, translate into support for the tax.
Keywords: D72; H23; Q54; Q58; 330; Pigouvian taxes; policy packaging; public support; lab experiment; tax aversion